2019
DOI: 10.1186/s13756-019-0588-1
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility profile of selected Enterobacteriaceae in wastewater samples from health facilities, abattoir, downstream rivers and a WWTP in Addis Ababa, Ethiopia

Abstract: Background Evaluation of antimicrobial susceptibility profile of various bacterial pathogens in the health facilities, abattoirs and related environment is important to assess potential risk of dissemination of resistant pathogens to the environment. There is limited information about antimicrobial susceptibility profile of common Enterobacteriaceae in waste water samples from hospitals, abattoirs and the downstream water bodies in Addis Ababa. The present study assessed antimicrobial susceptibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
29
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 37 publications
10
29
2
Order By: Relevance
“…The MALDI-TOF confirmation of the identities of the presumptive Enterobacteriaceae isolated revealed that E. coli was mostly detected in this study with a 33% detection rate. A similar result was reported by (10) and (11). This high detection rate of E. coli when considered with the other members of Enterobacteriaceae detected is, however, unsurprising as E. coli is a common commensal organism in the gastrointestinal tracts of animals as well as humans.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The MALDI-TOF confirmation of the identities of the presumptive Enterobacteriaceae isolated revealed that E. coli was mostly detected in this study with a 33% detection rate. A similar result was reported by (10) and (11). This high detection rate of E. coli when considered with the other members of Enterobacteriaceae detected is, however, unsurprising as E. coli is a common commensal organism in the gastrointestinal tracts of animals as well as humans.…”
Section: Discussionsupporting
confidence: 88%
“…Titilawo and colleagues (9) also reported multiple antimicrobial resistances ranging from three to nine antimicrobials from E. coli isolated from some rivers in Nigeria. Toroglu and colleagues (62) reported MDR in the members of Enterobacteriaceae recovered from some rivers in Turkey (62) with similar results being reported by(63) and(11) in the rivers of Bangladesh and Ethiopia respectively.Various human activities contributes to the diverse MARPs observed in rivers. One of the most important being the discharge of wastewaters as rivers are the primary recipients of effluents from sewage(11,64).…”
supporting
confidence: 72%
See 2 more Smart Citations
“…Over the last two to three years, interesting investigations on the treatment of hospital effluent have been carried out worldwide: consolidated and modified/enhanced technologies as well as new solutions have been tested on the effluent of specific wards, the whole healthcare structure, nursing homes specialised in psychiatric diseases ( 22 ), ( 23 ) or service units such as laundry ( 24 ). They have not only taken place in countries where studies or investigations on hospital effluent have also been carried out, but also in new ones, such as Ethiopia ( 25 ), Columbia ( 5 ), India ( 26 ), Iran ( 27 ), ( 28 ), Costa Rica ( 29 ) and Thailand ( 21 ). This demonstrates the increasing interest in the management and treatment of healthcare structure effluent by researchers, practitioners, policy makers and administrative staff, both in developed and developing countries.…”
Section: Perspectives In the Treatment Of Hospital Effluentmentioning
confidence: 99%